Efficacy of pamidronate in pediatric osteosarcoma patients with low bone mineral density - Se Won Lim; Ju Hyun Ahn; Aery Choi; Wan Hyeong Cho; Jun Ah Lee; Dong Ho Kim; Ju-Hee Seo; Jung Sub Lim (Korean Society of Pediatric Endocrinology, 2016)
PurposeMost surviving pediatric osteosarcoma patients experience osteoporosis, bone pain, and pathologic fracture during and after therapy. The aim of this study was to evaluate the efficacy and side effects of pamidronate therapy in these patients.MethodsNine osteosarcoma patients (12.8±1.6 years of age; 5 boys and 4 girls) who had a history of nontraumatic fracture or severe pain after completing chemotherapy were included. Intravenous pamidronate (1.5 mg/kg) was given every 6 weeks for 4 to 6 cycles. Bone mineral density (BMD) of the lumbar spine was measured by dual-energy x-ray absorptiometry. Clinical outcomes including acute side effects were also evaluated.ResultsAfter pamidronate treatments, all patients experienced decreased pain. Seven of 9 patients could walk without a crutch. The BMD of lumbar spine was increased by 0.108±0.062 mg/cm2 after 8.4±1.0 months (n=8, P=0.017) and the mean z-score improved from -2.14±0.94 to -1.76±0.95 (P=0.161). Six patients (67%) had an acute-phase reaction, and 2 patients had symptomatic hypocalcemia.ConclusionPamidronate appears to be safe and effective for the treatment of osteosarcoma in children with low BMD and bone pain.